Development of Recycling Water Media Video Learning to Improve Processes and Learning Outcomes IPA Elementary Students - Fachrur Rozie (Universitas Negeri Malang, 2014)
Pengembangan Media Video Pembelajaran Daur Air untuk Meningkatkan Proses dan Hasil Belajar IPA Siswa SD Abstract: This study aims to produce instructional video media with material recycled water eligible to improve the learning process and result graders of SDN Bintoro 02 Jember. Model used development is development model modified Borg & Gall. Feasibility tested on three validator. Effectiveness, keterterapan, and attractiveness tested on teachers and students were observed by three observers. Instruments collected in the study include (1) the results of the feasibility trial, (2) the attractiveness of the test results, (3) the results of tests keterterapan, and (4) the results of testing the attractiveness analyzed using a formula developed. Results of field trials showed that the water cycle instructional video media can enhance the learning process and result IPA Elementary School fifth grade students Bintoro 02 Jember. Key words: instructional video media, the water cycle, learning science. Abstrak: Penelitian ini bertujuan menghasilkan media video pembelajaran dengan materi daur air yang layak untuk meningkatkan proses dan hasil belajar siswa kelas V SDN Bintoro 02 Jember. Model pengembangan yang digunakan adalah model pengembangan Borg&Gall yang dimodifikasi. Kelayakan diujicobakan pada tiga validator. Keefektifan, keterterapan, dan kemenarikan diujicobakan pada guru dan siswa yang diobservasi oleh tiga orang observer. Instrumen yang dikumpulkan dalam penelitian meliputi (1) hasil ujicoba kelayakan, (2) hasil ujicoba kemenarikan, (3) hasil ujicoba keterterapan, dan (4) hasil ujicoba kemenarikan dianalisis menggunakan rumus yang dikembangkan. Hasil ujicoba lapangan menunjukkan bahwa media video pembelajaran daur air dapat meningkatkan proses dan hasil belajar IPA siswa kelas V SD Negeri Bintoro 02 Jember. Kata kunci: media video pembelajaran, daur air, pembelajaran IPA